Role of T‐box genes in cancer, epithelial‐mesenchymal transition, and cancer stem cells. Issue 2 (13th December 2021) - Niu, Gengle; Hao, Jin; Sheng, Surui; Wen, Fangyuan
Abstract: Sharing a common DNA binding motif called T‐box, transcription factor T‐box gene family controls embryonic development and is also involved in cancer progression and metastasis. Cancer metastasis shows therapy resistance and involves complex processes. Among them, epithelial‐mesenchymal transition (EMT) triggers cancer cell invasiveness and the acquisition of stemness of cancer cells, called cancer stem cells (CSCs). CSCs are a small fraction of tumor bulk and are capable of self‐renewal and tumorsphere formation. Recent progress has highlighted the critical roles of T‐box genes in cancer progression, EMT, and CSC function, and such regulatory functions of T‐box genes have emerged as potential therapeutic candidates for cancer. Herein we summarize the current understanding of the regulatory mechanisms of T‐box genes in cancer, EMT, and CSCs, and discuss the implications of targeting T‐box genes as anticancer therapeutics.